Emergency Nurses’ Perceptions of Supportive Behaviors and Burdens in Providing End-Of-Life Care - Santi Ariyanti; Etika Emaliyawati; Ristina Mirwanti (Universitas Padjadjaran, 2019)
The high mortality rate in the Emergency Department (ED) is consistent with the high demand for the end of life (EOL) care. However, ED work system required to live-saving quickly and precisely. It affects the quality of EOL care. The purpose of this study was to determine nurses’ perceptions in ED related to supportive behaviors (SB) and burdens in providing EOL care to dying patients. The descriptive-quantitative method was used with a cross-sectional approach in 50 nurses Emergency Department at one of the tertiary hospitals in Indonesia. The samples were chosen using the total sampling technique. Data collection used emergency nurse perceptions of end of life care questionnaire. Data were analyzed using univariate analysis in the form of distribution, frequency, and mean. The result of the study showed that the three largest obstacles in EOL care were: ED nurses’ work loads (mean=10.626), intra-family disagreements (mean=9.802), and deal with angry of family members (mean=9.472). The three largest supportive behaviors were teaching families how to act (mean=11.962), allowing family members adequate time with the patient after a patient died (mean=11.09), and good collaboration from health professionals (mean=10.886). According to this research, further studies are needed to minimize obstacles and improve supportive behaviors related to the nurse’s workload, the provision of spiritual teams, special training for the nurse and the provision of special rooms for EOL patients and their families.